Morpho-anatomical investigation on stipules, colleters and leaves of Rhizophora spp. in Pagapas Bay, Calatagan, Batangas, Philippines - Endonela, Leah E. (Transactions of the National Academy of Science and Technology, 2011)
The morphology and anatomy of stipules, colleters and leaves of four identified Rhizophora species: R. apucilata, R. mucronata, R. stylosa, and putative hybrid R. x lamarckii in Pagaspas Bay, Calatagan, Batangas, Philippines were investigated. Stipule color and size vary winthin species. The stipule has mono-layered epidermis covered with thick cuticular wax, distinct aggregate sclereid ideoblasts, well-developed vascular bundle, and multilayered hypodermis. The variations in color, exudates consistency and series of number of aggregate colleters were elucidated. Colleters have central axis composed of slender, elongated cells surrounded by palisade-like epidermis. Differences in leaf morpho-anatomy including leaf shape, leaf structure, mucus cells, vascular bundle, stomata apparatus and corkwarts were also observed in the four Rhizophora species. In general, Rhizophora leaf consists of thick cuticle, single layer epidermis, 6 to 7 layers of hypodermis, funnel-shaped mucus cells, parallel columns of four layers palisade mesophyll, and varied layers of spongy mesophyll. The presence of druse crystals in stipule and leaves is common. Features of the stomatal apparatus including guard cells lignin thickness, subsidiary cells arrangement and stomatal aperture are considered diagnostic. Guard cells have a pair of inner and outer cuticular ridges. Stomata and corkwarts, which developed from stomata as the leaves mature, are concentrated only in abaxial leaf surface. These morpho-anatomical characteristics of Rhizophora species exemplified the structural modifications that enabled them to adapt to the physiologically dry, saline mangrove environment.